Robust decision-making design for sustainable pedestrian concrete bridges. (15th April 2020) - Penadés-Plà, Vicent; Yepes, Víctor; García-Segura, Tatiana
Highlights: A new methodology is created to reach robust solutions against different opinions. The methodology reduces subjective assessment in the decision-making process. The results show that this methodology reduces an initial set of 500 bridges to 4. The selected bridge has a low mean sustainable index and coefficient of variance. Abstract: In recent years, there is a trend toward the construction of sustainable structures. The goal of sustainability in structures involves several criteria that are normally opposed, leading to a decision-making process. In this process, there is a subjective portion that cannot be eliminated, such as qualitative criteria assessment of and assigning criteria importance. In these cases, decision-makers become part of the decision-making process, assessing it according to their preferences. In this work, a methodology to reduce the participation of decision-makers in achieving the goal of sustainability in structures is proposed. For this purpose, principal component analysis, kriging-based optimization, and the analytical hierarchy process are used. Principal component analysis is used to reduce the complexity of the problem according to the highly correlated criteria. Kriging-based optimization obtains sustainable solutions depending on all the perspectives of sustainability. Finally, the analytical hierarchy process is applied to reduce the optimized sustainable solutions according to the decision-maker's views. This methodology is applied a continuous concrete box-girder pedestrian bridge deck to reach sustainable designs. This methodology allows a reduction of the complexity of the decision-making problem and also obtains sustainable robust solutions.